Epidemiological profile of gestational and congenital syphilis in the state of Mato Grosso, Brazil (Research, Society and Development, 2022)
Introduction: Syphilis is a disease transmitted mainly sexually and vertically. Congenital syphilis is preventable when a pregnant woman is treated, warning about the importance of prenatal screening. Objective: To describe the epidemiological profile of gestational and congenital syphilis in the state of Mato Grosso - Brazil. Methodology: A descriptive cross-sectional study with a quantitative approach, using secondary data from the Notifiable Diseases Information System (SINAN), from 2011 to 2020. Results: 5120 cases of gestational syphilis and 2320 cases of syphilis were reported congenital in the state of Mato Grosso. The induced cases increased over the years, with notification peak of gestational syphilis in the year 2019 with 942 (18%) cases and congenital syphilis in the year of 2018 with 322 (14%) cases. Most women affected by gestational syphilis were young, with low education, mixed race, who underwent prenatal care, did not have their partners treated concomitantly and had a late diagnosis after the first trimester. Patients with congenital syphilis were mostly diagnosed early. Conclusion: The findings change flaws in prenatal care and the need for greater investments in innovative actions in order to reduce vertical transmission of syphilis.